A Study on the Eigenmodes of the Rectangular Cavity - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
In this study, finite Element method has been carried out to investigate the eigen properties of the rectangular cavity. Because the horizontal length is much larger than that of vertical one, eigenmodes take on various forms in the horizontal direction. The physical properties of rectangular cavities have been considered basing on the higher-order eigenmodes including the ground state. The eigenmodes have been divided into two classes: transverse electric modes and transverse magnetic modes. These classes were depended on the boundary condition imposed on the cavity surface. The eigenmodes have been described with the electric field, electric potential and electric equipotential contour. The eigenmode was determined by comparing and compensating the electric field and potential each other. These results have been revealed by schematic representations.